Fra sentimental magtesløshed til kolonial rædsel: Litterære skildringer af slaveri og slaveoprør på Jamaica - Montesinos Volder, Stephanie (K&K - Kultur og Klasse, 2021)
The article explores the use of sentimental and Gothic emotionality in William Earle’s epistolary novel Obi or, The History of Three-Fingered Jack (1800). Literature about colonial slavery challenges previous notions of the relationship between the sentimental and the Gothic as literary traditions and modes of writing. The sentimental narrative often involves morally edifying tears and compassionate attempts to alleviate the suffering of others. In Obi’s Gothic passages, however, extreme sensitivity proves powerless or downright dangerous as tears and prayers for mercy overwhelm the senses of the sympathetic protagonists. In Earle’s literary representation of slavery and slave revolt, the Gothic mode demonizes the slave trade and highlights the breakdown of sentimental benevolence and its theatrical codes of emotional display. Thus, Earle’s novel complicates Lynn Festa’s reading of sentimental sympathy and pity as feelings that construct hierarchical relations of empire. In Obi, sentimental emotionality does not support racial inequality but is insufficient, nonetheless, as a model for useful social action.